Learning across the early childhood curriculum - Cohen, Lynn E.; Waite-Stupiansky, Sandra (Bingley, U.K. : Emerald, 2013)
Education, according to John Dewey, should be viewed as dynamic and ongoing with direct teaching of integrated content knowledge. This volume offers readers an examination of the content areas in early childhood curriculum that honor Deweys belief in active, integrated learning. When young children learn in a way that is most natural to them, they unconsciously integrate subject areas into a complex whole based on their current interests. The ability to apply and integrate academic skills such as language arts, numeracy, scientific investigation, social studies, technology, and health and physical education is key to building capacity for future learning. Teachers who follow this method of teaching view curriculum as a fully spun web that incorporates a number of subject matter components at one time, and ensure that the content areas are taught. Topics addressed in this volume include: The role of STEM, teacher preparation, communication and technology.
Theory guided professional development in early childhood science education / Soo-Young Hong, Julia Torquati, Victoria J. Molfese -- Engaging young learners in integration through mathematical modeling : asking big questions, finding answers, and doing big thinking / Lucia M. Flevares, Jamie R. Schiff -- Physical-knowledge activities : play before the differentiation of knowledge into subjects / Constance Kamii -- Content knowledge and vocabulary learning in nature : becoming a nature scientist! / Myae Han, Nancy Edwards, Carol Vukelich -- The role of STEM (or STEAM) in the early childhood setting / Karen W. Lindeman, Michael Jabot, Mira T. Berkley -- John Dewey and Reggio Emilia : using the arts to build a learning community / Joy Faini Saab, Sam F. Stack -- Tapping the arts to teach Rs : arts-integrated early childhood education / Eleanor D. Brown -- Integrating early literacy and other content curriculum in an era of increased accountability : a review of the literature / Elizabeth Anderson, Nicole Fenty.
Includes index.
Keywords: Education -- Teaching Methods & Materials -- General; Teaching skills & techniques; Early childhood education -- Curricula